Organization and Information in the Fight against Crime: An Evaluation of the Integration of Police Forces in the State of Minas Gerais, Brazil - Rodrigo R. Soares; Igor Viveiros (Pontifícia Universidade Católica do Rio de Janeiro (PUC-Rio), Departamento de Economia, 2010)
This paper explores the experience of information sharing, coordination, and integration of actions of the Civil and Military Polices in the state of Minas Gerais, Brazil, in the context of the IGESP program. The IGESP is based on the introduction of information management systems and organizational changes akin to those associated with COMPSTAT. All the evidence presented points to a causal effect of the IGESP on crime. The most conservative estimates indicate a reduction of 24% in property crimes and 13% in personal crimes. There is also evidence that the IGESP is associated with improved police response, measured by apprehension of weapons and clearance rates. We present one of the first set of causal estimates – with a clear identification strategy – of the impact of COMPSTAT-like programs. The results suggest that the coordination and informational gains represented by the program may constitute a first-order factor in a successful policy for fighting crime.
Keywords: H11; K00; K42; 330; crime; police; Brazil; COMPSTAT; impact evaluation JEL Codes: H11; K00; K42; Kriminalpolitik; Polizei; Militär; Wissenstransfer; Informationssystem; Kausalanalyse; Kriminalität; Schätzung; Brasilien; Minas Gerais